Non-Vent Megafaunal Communities on the Endeavour and Middle Valley Segments of the Juan de Fuca Ridge, Northeast Pacific Ocean - Neufeld, Monika; Metaxas, Anna; Jamieson, John W. (Frontiers in Marine Science, 2022)
There has been increasing interest in mining polymetallic sulfide deposits at deep-sea inactive hydrothermal vents, leading to the development of regulations to minimize risk to the marine environment. While an extensive body of literature exists on the ecological communities at active vents, fauna at inactive hydrothermal vents and the vent periphery are poorly described and their vulnerability to disturbance is unknown. We examined patterns in abundance of non-vent epibenthic megafauna on two segments of the Juan de Fuca Ridge, Northeast Pacific Ocean. Video footage was collected by the remotely operated vehicle ROPOS during four dives at the Endeavour Segment and two dives at Middle Valley in August 2016. At the Endeavour Segment, the substrate is characterized predominantly by basalt and edifices of hydrothermal sulfide that range in hydrothermal activity from inactive to vigorous, high-temperature venting. In contrast, Middle Valley is heavily sedimented and most hydrothermal activity is low-temperature diffuse flow. While inactive substrates at both sites harboured slow-growing sessile fauna, the dominant members of the community differed between sites. At Endeavour, the most abundant morphotaxa included rossellid vase sponges, alcyonacean corals, and crinoids. Estimated richness and total abundance of morphotaxa was higher on hard substrates than sedimented substrates and highest on inactive chimneys. At Middle Valley, the most abundant morphotaxa included antipatharian corals, anemones, and ascidians. Species richness was higher on inactive chimneys and mixed substrates than sediment. The abundance of some megafauna varied with proximity to active vents. At Endeavour, deep-water corals were nearly absent within 25 m of active chimneys and very few occurred between 26 and 50 m from active chimneys. Rossellid vase sponges were in low abundance within 25 m of active chimneys but were more abundant than corals at 26-50 m from active chimneys. This project contributes baseline data on megafaunal assemblages on inactive hydrothermal vents and can provide the basis for more focused research on the structure and function of inactive vent ecosystems.